Impact of aerobic exercise on anxiety and neurobiological mechanisms in panic disorder: a mini-review - Machado, Sérgio (2019)
In the last few decades exercise has been explored as a potential tool to reduce symptoms experienced by patients with panic disorder (PD). This review aims to present the effects of exercise interventions on panic severity, and anxiety symptoms of patients with PD. A literature search was conducted using PubMeb and ISI Web of Science databases, with the search terms panic disorder and aerobic exercise, exercise therapy, physical fitness, physical activity, aerobic training. Acute studies suggest that exercise immediately increases panic-related symptoms, but allows the reduction of artificially induced increase panic attacks and anxiety. There is still no clear evidence indicating that regular exercise programs reduce panic-related symptoms, but it seems that this intervention is effective to improve global anxiety measures. In addition, exercise seems to induce neurobiological effects that influence on several neural mechanisms related to anxiety disorders, such as increase of monoamine levels and brain-derived neurotrophic factor (BDNF).Both aerobic exercise and regular aerobic exercise seem to be an appropriate intervention to promote improvements in the severity of anxiety symptoms in PD patients. It is suggested a greater control in the prescription of aerobic exercise, to bring promising answers regarding the efficacy of exercise on symptoms in patients with PD.